Research Libraries Group: Free 30-day Trials for RLG's Citadel Service - Not applicable (Issues in Science and Technology Librarianship)
CitaDel is the new article-citation and document-delivery service from the Research Libraries Group (RLG). Through CitaDel, libraries, universities, and other institutions can make citation databases available to their users over a library or campuswide network without having to load and maintain large files locally. Free 30-day trials of CitaDel's citation files are now available to interested institutions.